PENGATURAN HUKUM POSITIF DI INDONESIA TERHADAP PEREMPUAN HAMIL KARENA ZINA - Jamil, Sukran; Saputra, Hendra Adi (Jurnal Muhakkamah, 2020)
Adultery is a crime that violates decency. Adultery can lead to pregnancy and have children so that other problems arise with the status of the relationship between men and women who commit adultery and what about the status of children who come from adultery. So that raises a problem how is the positive legal arrangements in Indonesia for pregnant women due to adultery? Adultery in the sense of criminal law is different from adultery in terms of Islamic law, in criminal law a person who is married has sex with someone else's partner is called adultery while in Islamic law a person who conducts a relationship like a husband and wife both the status of the person is married and unmarried then considered adultery. And if she is pregnant, she must wait for the iddah before she is married to someone else. But according to KHI, it is permissible for pregnant women to be married because adultery is married.